The experience of young carers in Australia: a qualitative systematic review and meta-ethnographic synthesis - Owen Walker; Richard Moulding; Jonathan Mason (Australian Journal of Psychology)
Background Many people require additional care and support to meet their personal, health and psychosocial needs. Sometimes that responsibility falls to young people within their families. The research to date indicates that the impact on these young people can be significant, however no comprehensive reviews have yet examined this in Australian participants.Objective Given the personal, subjective experience of caring, this study systematically reviews the qualitative literature on Australian youth under 25 who provide an informal caring role, using a meta-ethnographic approach.Method Qualitative studies published since 2002 using Australian participants were included. The databases used included: Psychology and Behavioural Sciences Collection, PsycInfo, PsycArticles, MEDLINE Complete, Academic Search Complete, CINAHL, and Child Development & Adolescent Studies. Quality ratings and risk of bias are discussed.Results Seventeen studies were included in the final analysis, representing the experiences of 531 young carers. The results suggest that the young carer experience is profound and impacts a range of domains, including social, academic, and psychological. The impacts are largely perceived as disadvantageous, although some positive outcomes are discussed.Conclusion On the basis of the findings, the review concludes by offering a model to conceptualise the Australian young carer phenomenon.